Correlating electrical dysfunctions and structural remodeling in Arrhythmogenic Mouse Hearts by advanced optical methods. (10th June 2022) - Giardini, F; Olianti, C; Biasci, V; Arecchi, G; Zaglia, T; Mongillo, M; Cerbai, E; Zgierski-Johnston, C; Kohl, P; Sacconi, L
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – EU funding. Main funding source(s): European Union's Horizon 2020 research and innovation programme - No 952166 (REPAIR) Regione Toscana - Bando Ricerca Salute 2018 - PERCARE project. Severe remodeling processes may occur in the heart due to both genetic and non-genetic diseases. Structural remodeling, such as collagen deposition (fibrosis) and cellular misalignment, can affect electrical conduction at different orders of magnitude and, eventually, lead to arrhythmias. In this scenario, arrhythmogenic cardiomyopathy (ACM) is an inherited heart disease that involves ventricular dysfunction, arrhythmias, and localized replacement of contractile fibers with fibrofatty scar tissue. Unfortunately, nowadays, predicting the impact of fine structural alterations on the electrical dysfunction in entire organs is challenging, due to the inefficacy of standard imaging methods in performing high-resolution three-dimensional reconstructions in massive tissues. In this work, we developed a new full-optical correlative approach to quantify and integrate the electrical dysfunctions with three-dimensional structural reconstructions of entire hearts, both in controls and in a mouse model of ACM. We combined optical mapping of the action potential propagation (APP) with advances in tissue clearing and light-sheet microscopy techniques. First, we employed an optical platform to map and analyze the APP in Langendorff-perfused hearts. Then, we optimized the SHIELD procedure for the clearing of cardiac tissue, thus converting the previously electrically characterized samples into well-preserved and fully-transparent specimens. A high-throughput light-sheet microscope has been developed following the mesoSPIM project: the conceived microscope allows the reconstruction of the whole mouse heart with a micrometric resolution allowing fine quantification of myocytes alignment and fibrosis deposition across the organ. Finally, we developed a software pipeline that employs high-resolution 3D images to analyze and co-register APP maps with the 3D anatomy, contractile fibers disarray, and fibrosis deposition on each heart. We believe that this promising methodological framework will allow clarifying the involvement of fine structural alterations in the electrical dysfunctions, thus enabling a unified investigation of the structural causes that lead to electrical and mechanical alterations after the tissue remodeling.